Low back pain among nurses at Srinagarind Hospital Khonkaen, University, Thailand, 1994 Uraiwon Chatchawan. - Uraiwon,Chatchawan
A cross-sectional study of 462 Registered nurses (RN) and 294 Practical nurses (PN) in Srinagarind Hospital was conducted to estimate the prevalence of low back pain and identify factors associated with it. Data were gathered primarily through self-administered questionnaires.This study found that 11.7(83 cases) of the nurses had experienced low back pain, defined as pain exceeding 2 weeks within the past 6 months before the interview. Nurses in the older age group (30 years old) have a LBP prevalence of 13.1, a little higher than the younger age group (10.0). Also, nurses who have adequate exercise (11.2) have less LBP than those who have inadequate exercise (13.9). Obese nurses have LBP prevalence (8.2) less than those who are of normal weight (11.8). In terms of type of nurses, the prevalence of LBP was 13.0among PN and 10.6among RN. Nurses who have been working longer (9 years or more) in the nursing profession have a prevalence of 12.1, slightly higher than those who have been working for a shorter time (11.0). Contrary to earlier reported, among nurses who were categorized to have a lighter work-load, the prevalence of LBP was slightly higher than in those who have heavier work-load (10.8).Of the different exposure variables examined, only carrying of heavy objects or patients for a prolonged period of time per shift was statistically associated with LBP. The other factors, like duration of employment, ward assignment, obesity, sitting, standing, and walking during work did not significantly influence LBP.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Backache